DEVELOPMENT OF AN ECONOMIC MECHANISM FOR THE REFORM OF NATURAL TECHNOLOGICAL MONOPOLIES - A. N. Ryakhovskaya (Финансы: теория и практика, 2017)
The paper examines the results of the reform in the power engineering sector, the government’s attempt to stabilize the economic state of the industry, particularly through the consolidation of structures developed in the course of the reform and going back in some instances to some of the pre-reform positions.The economic basis of activities in the public utility sector is substantiated; the specifics of the utilities production, public services and the utilities market are discussed. A particular emphasis is laid on the potential development of market relations in natural technological type monopolies whose existence depends on the level of the state’s economy development, equipment and related technologies. The performance efficiency of the private business and its obligations assumed in the course of the power industry reform are analyzed.